PENERAPAN RESTITUSI TERHADAP ANAK YANG MENJADI KORBAN KEJAHATAN SEKSUAL (Studi Penelitian Di Pengadilan Negeri Bireuen) - Ananda Bagus Prayuda (Yayasan Daarul Huda Kruengmane, 2022)
Article 71D paragraph (1) of the Law of the Republic of Indonesia Number 35oof 2014 concerning Amendmentssto Law Number 23 of 2002 concerning Childl Protection states